A Brief Review of Power Quality Issues Emerged due to Modernization of Power System Infrastructure - Mohit Bajaj (International Transactions on Electrical Engineering and Computer Science, 2022)
The architecture of power systems is evolving daily due to technological advancements aimed at reducing energy consumption and improving the environment. However, this improvement in the architecture of the network has affected the quality of the electricity and is producing several problems associated with the quality of power supplied. In a broad sense, the recent standard procedures for power generation, transmission and distribution are the root cause of the recently discovered problems with power quality. Investigating these problems is essential to accurately forecast the stochastic impacts on today network's functioning and locate the best remedy for these problems. This study includes a discussion on quality challenges that evolved due to modernization in the infrastructure of power network and an evaluation of the latest solutions presented in the literature to overcome those difficulties. This paper also makes recommendations for the future scope of research that should be done to address these new power quality problems.